PELAKSANAAN PROGRAM ADIWIYATA DI KOTA PEKANBARU TAHUN 2016 - Yulanda, Sendu; Febrina, Rury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The main activity of Adiwiyata program is to realize the institution a caring andcultured school environment for primary schools and medium enterprises in Indonesia. To developprograms and activities within Adiwiyata program must be based on basic and living norms. Thebasic norms of the Adiwiyata program include togetherness, openness, honesty, fairness, andsustainability of environmental functions and resources natural.This study aims to determine the implementation of Adiwiyata program in Pekanbaru CityYear 2016 . This research uses qualitative research method with descriptive research type. Thismethod aims to get a true picture of the implementation of Adiwiyata program in Pekanbaru City in2016 . The implementation of Adiwiyata program in Pekanbaru City in 2016 is done by severalsteps, first is to form Adiwiyata team consisting of assessment team, team of supervisor andtechnical team. This Adiwiyata Team will be implementing, socializing, appraising and givingawards to schools that follow adiwiyata program. The second step that must be done inimplementing Adiwiyata program is developing and implementing Adiwiyata program. There are 4components and standard of adiwiyata program in developing and implementing Adiwiyataprogram , they are: environmentally sound school policy, environment based curriculumdevelopment, management of environmentally friendly support facilities and participative basedenvironmental activities . Third, socializing Adiwiyata program. Socialization here is a form ofpolicy delivery of adiwiyata program in Pekanbaru City to all citizens of the school well and bena r.Fourth, coaching. Implementation of school coaching that organizes Adiwiyata program inPekanbaru City has reached all schools. Fifth, assessment, evaluation of the results of guidanceand school proposal adiwiyata . By 2016 there are 82 schools that have passed the evaluation of theAdiwiyata school assessment team. Sixth, awarding Adiwiyata school award . In 2011-2016 therewere 109 schools that were nominated for school with a healthy environment. Factors affecting theimplementation of Adiwiyata program in Pekanbaru City Year 2016 namely communication,resources, in sposition, and bureaucratic structure. The four components have been implementedproperly so that the implementation of Adiwiyata program in Pekanbaru City of 2016 is done well.Keyword: Adiwiyata Program .